Respon Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill) Terhadap Pemberian Pupuk Kompos - Susanti, Sari (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Tomatoes (Lycopersicum esculentum Mill), are one of the agricultural commodities that are popular with the public because they taste delicious and fresh and contain various kinds of vitamins. Efforts that can be made to increase the productivity of tomato plants include applying fertilizer. The fertilizer given can be organic fertilizer and inorganic fertilizer. Providing compost fertilizer is highly recommended, especially to improve the physical, chemical and biological properties of the soil, as a medium for plant growth. The aim of this research is to obtain the best dose of compost for the growth and yield of tomato plants (Lycopersicum esculentun Mill). This research is an experiment based on a completely randomized design (CRD) with six treatments and four replications. With compost treatment: 0 tons/ha, 5 tons/ha, 10 tons/ha, 15 tons/ha, 20 tons/ha and 25 tons/ha. The results of the research showed that observing the number of primary branches, number of flower clusters and fruit weight per plant had a significant difference, whereas observing plant height, flowering age, harvest age and number of fruit per plant had no significantly different influence on tomato plants.